A recipe for success: Asia's F&B franchising - Koh, Kek Sin (Institutional Knowledge at Singapore Management University, 2019)
Asian food and beverage (F&B) brands are exploding in popularity all over the world. Since 1999, Asian fast food restaurants have grown by 500 percent globally, making it the single fastest-growing food category, outstripping the growth of the next four, i.e. Middle Eastern, Chicken, Pizza, and Latin.1 At the same time, there is a huge opportunity for F&B franchising in Asia Pacific—over the past decade, the sector has flourished with the entry and expansion of both international and Asian brands, and in 2016, the restaurant industry in this region was estimated to be worth some US$1.5 trillion.2 Going forward, there is more space for growth with the continuing rise of the middle class in Asia. However, one must be careful not to treat Asia in a homogeneous way, as consumer expectations and preferences, and a brand’s business model, could vary signifi cantly between developed nations, such as Japan, Korea and Singapore, and the developing countries in the region.